PESAN MORAL CERITA RAKYAT RIAU SEBAGAI IDE SENI LUKIS REALIS KONTEMPORER - Andini Kurnia Putri, Drs, Irwan, M.Sn., Drs. Erfahmi, M.Sn. (Serupa The Journal of Art Education, 2017)
This thesis aims to visualize the moral message of folklore in Riau through ontemporary realist paintingto be used aspreservation of cultural and moral education for human life. The method of creating art works starting from the preparation, elaboration, then synthesis, namely, conducting elections moral message of folklore in Riau as Batang Tuaka, Batu belah batu batangkup, Putri Kuning, Putri Mambang Linau and Bujang Buta. Furthermore, the realization of the concept and final settlement to the exhibition.Painting reveals the message of moral such as would change the fate, do not forgetting themselves, do not be envy, do not run away from trouble, do not takethe property of others, do not leave the family, do not break a promise, and do not revenge.Keywords: Moral Folklore Riau, Contemporary Realist Painting